USE OF SYNKINESIA IN THE REHABILITATION OF MOTOR DISORDERS OF THE MAXILLFACIAL AREA - Петров, Константин Борисович; Митичкина, Татьяна Векентьевна; Ивонина, Наталья Анатольевна; Попова, Наталья Васильевна (Medicine in Kuzbass, 2022)
Effective kinesitherapy of peripheral and central paralysis of mimic, masticatory, lingual and laryngeal-pharyngeal muscles require an in-depth study of the features of the friendly work of these muscles in normal and pathological conditions.Objective – to acquaint rehabilitation specialists with the motor automatisms of the brachiofacial area and show the principles of their practical use.Material. More than seventy literature sources on involuntary activity of the muscles of the maxillofacial region and adjacent regions were studied, in addition, their own experience in the rehabilitation of patients with peripheral neuropathies of the facial nerve, as well as with bulbar and pseudobulbar syndrome, was summarized.Results. The study showed that the face, neck and hand are much more closely involved than other parts of the body in a variety of mesencephalic-bulbar automatisms that occur both in the norm (ontogenetic and psychosomatic synkinesis, postural-oculomotor and postural-mandibular reflexes) and in pathology (stem orbito-facial synkinesis, reflexes of oral automatism).Conclusion. Many friendly movements can be used in the development of kinesitherapy techniques for movement disorders, including those in the maxillofacial area. The better the physical therapist is familiar with the features of the existing or potentially available to the patient reflex activity in the part of the body being rehabilitated, the more effective the rehabilitation treatment will be.
Keywords: kinesitherapy; bulbar palsy; pseudobulbar palsy; neuropathy of the facial nerve; rehabilitation; synergy; synkinesis